2017
DOI: 10.1108/ijwhm-07-2017-0050
|View full text |Cite
|
Sign up to set email alerts
|

Medical and allied health staff self-reported long-term conditions

Abstract: Purpose The purpose of this paper is to describe the self-reported long-term conditions of medical officers and allied health staff working in a regional public health service in northern Australia and how these conditions are managed. Design/methodology/approach A cross-sectional survey design was used. The sample was all medical officers and allied health staff employed in mid-2015. Findings Of the 365 respondents, 217 (59.5 per cent) reported having at least one long-term condition. There was a statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Potentially, 927 administration staff had an opportunity to respond to the invitation to complete their questionnaire during the four-week data collection period. A total of 328 completed questionnaires were submitted, a response rate of 35 per cent which was similar to previous similar surveys in this health service (Smyth et al , 2016; Smyth et al , 2017).…”
Section: Resultssupporting
confidence: 64%
See 3 more Smart Citations
“…Potentially, 927 administration staff had an opportunity to respond to the invitation to complete their questionnaire during the four-week data collection period. A total of 328 completed questionnaires were submitted, a response rate of 35 per cent which was similar to previous similar surveys in this health service (Smyth et al , 2016; Smyth et al , 2017).…”
Section: Resultssupporting
confidence: 64%
“…The study describes the self-reported long-term conditions that administrative staff working in a large regional health service manage on a day-to-day basis. The proportion of administrative staff without a long-term condition was found to be less than that of the other major staff groups within the same health service (Smyth et al , 2016; Smyth et al , 2017). In this study, musculoskeletal disorders were the major category of self-reported long-term conditions.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…No other studies were found which specifically compared disclosure of long-term conditions among medical officers, nurses, midwives and allied health professional staff. Indeed, previous studies have highlighted the paucity of robust evidence regarding the prevalence of long-term conditions, particularly physical co-morbidities, among health professional staff (Smyth et al, 2016;Smyth et al, 2017). By contrast, many studies have reported the prevalence of mental health conditions such as psychological distress, depression or depressive symptoms, and suicide or suicidal ideation amongst medical staff (Schwenk et al, 2008;Bailey et al, 2018), nurses (Cheung and Yip, 2015) and midwives (Creedy et al, 2017).…”
Section: Introductionmentioning
confidence: 99%